2022
DOI: 10.1101/2022.10.12.511902
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Olfactory chemosensation extends lifespan through TGF-β signaling and UPR activation

Abstract: Animals rely on chemosensory cues to survive in pathogen-rich environments. InC. elegans, pathogenic bacteria are known to trigger aversive behaviors through neuronal perception, and to activate molecular defenses throughout the animal. This suggests that neurons may be able to coordinate the activation of organism-wide defensive responses upon pathogen perception. We find that exposure to volatile pathogen-associated compounds induces cell non-autonomous activation of the endoplasmic reticulum unfolded protei… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Some previous studies have examined molecules that are produced by P. aeruginosa and sensed by C. elegans. These studies identified several compounds that are repulsive to C. elegans and one molecule that is attractive, but without being able to eliminate production of these molecules from the bacteria, the actual activity of these molecules remained unclear 8,9,11,35 . Excitingly, we identified the nitrogen assimilation product, ammonia, as the major attractant that causes C. elegans to prefer P. aeruginosa over E. coli .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some previous studies have examined molecules that are produced by P. aeruginosa and sensed by C. elegans. These studies identified several compounds that are repulsive to C. elegans and one molecule that is attractive, but without being able to eliminate production of these molecules from the bacteria, the actual activity of these molecules remained unclear 8,9,11,35 . Excitingly, we identified the nitrogen assimilation product, ammonia, as the major attractant that causes C. elegans to prefer P. aeruginosa over E. coli .…”
Section: Discussionmentioning
confidence: 99%
“…C. elegans respond and chemotax toward volatile compounds using olfactory neurons that control their locomotion 4 . A number of C. elegans attractants and repellents have been defined, and some of these attractants and repellants have been shown to be produced by bacteria [4][5][6][7][8][9] . But the physiological importance of the production of specific bacterially-produced molecules for the chemotaxis of C. elegans towards specific bacterial species has remained largely elusive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A new study has now observed that olfactory chemosensation of pathogen-derived molecules by chemosensory neurons cause cell non-autonomous activation of the UPR ER in C. elegans . This is accompanied by lifespan extension and reduced accumulation of toxic polyglutamine expansions ( De-Souza et al, 2022a preprint). In parallel, another group observed that exposure to a specific odour (urine) extends the lifespan of female mice ( Garratt et al, 2022 preprint).…”
Section: Discoveriesmentioning
confidence: 99%
“…However, this approach is difficult to tune and the blood–brain barrier is a major obstacle in efforts to manipulate neurons. Works showing that neuronal proteostasis can be modulated by sensory inputs ( De-Souza et al, 2022a preprint; Ozbey et al, 2020 ) suggest that, if validated in mammals, targeting chemosensory neurons could be a strategy to bypass the blood–brain barrier to modulate brain proteostasis.…”
Section: Discoveriesmentioning
confidence: 99%